Preventing Youth Violence in a Multicultural Society. 2006
DOI: 10.1037/11380-002
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity, Social Group Membership, and Youth Violence.

Abstract: Research in the area of youth violence has identified multiple causes and pathways of development that lead to aggression, violence, and other problem behaviors (Patterson, DeBaryshe, & Ramsey, 1989;Tolan, Guerra, & Kendall, 1995). An array of risk and protective factors has been delineated emphasizing individual, peer, family, and community predictors. Given the disproportionate rates of youth violence among ethnic minority youth, it is particularly important to examine the salience of these risk factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…Although there was also a positive association between multiculturalism and ethnic identity, ethnic identity was not statistically associated with interpersonal violence. Whereas researchers have noted the importance of a multicultural context for ethnic identity development, the relation between ethnic identity and youth interpersonal violence is not altogether clear and conclusive since studies among Asians and Hispanic youth have yielded mixed results 22,34,35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was also a positive association between multiculturalism and ethnic identity, ethnic identity was not statistically associated with interpersonal violence. Whereas researchers have noted the importance of a multicultural context for ethnic identity development, the relation between ethnic identity and youth interpersonal violence is not altogether clear and conclusive since studies among Asians and Hispanic youth have yielded mixed results 22,34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Ethnic identity is another potential mediator linking multiculturalism and interpersonal violence. Although research has shown that positive identity development is protective against interpersonal violence, ethnic minority adolescents often have difficulty with developing a positive identity as they may feel that they are not supported or valued because of the presence of racism and marginalization in the mainstream American society 22 . Multiculturalism, however, is arguably supportive of an environment inclusive of individuals from various ethnicities and cultural backgrounds, thus facilitating positive ethnic identity development for all groups.…”
mentioning
confidence: 99%
“…30 In examining African Americans' healthy development, ethnic affirmation is consistently related to higher self-esteem and better academic achievement. 12,31 Studies on Latino populations have yielded mixed findings regarding the role of ethnic affirmation in development, with some studies reporting that ethnic affirmation predicts lower rates of delinquency, 32 and higher self-esteem, 12 but one study showing that ethnic affirmation is positively associated with deviant behaviors. 30 Although work with Asian Americans is more limited, studies have found that higher levels of ethnic affirmation are associated with less delinquency, 33 higher self-esteem, 12,34 and fewer depressive symptoms.…”
Section: The Role Of Ethnic Identity Among Ethnicmentioning
confidence: 99%
“…Des études soulignent que les jeunes associés à un gang de rue pré-sentent également un sentiment d'appartenance plus élevé envers leurs origines ethniques que ceux n'y étant pas associés (French, Kim et Pillado, 2006 ;Knight et al, 2012). L'homogénéité de la composition ethnique de plusieurs gangs peut amener les jeunes membres de ces groupes à s'y associer pour obtenir plus d'informations sur ce que cela signifie d'être d'une certaine origine ethnique, tout en offrant une plateforme pour commettre davantage d'actions délinquantes par l'entremise des activités liées aux gangs.…”
Section: Identité Ethnique Et Gang De Rueunclassified